The Influence Of Display Producton Towards Consumer Satisfaction At Togamas Supratman Bandung - BARAKOH, Rezky Afiahtul (PT Keberlanjutan Strategis Indonesia, 2021)
The purpose of this research is to determine the effect of display production to consumer satisfaction at Togamas Supratman Bandung. The research method used descriptive analysis method. Data collection techniques used library research and field research in the form of non-participant observation, structured interviews, and distributing questionnaires to 60 respondents. For data analysis used validity test, reliability test, hypothesis testing, correlation coefficient X on Y, significant test, simple linear regression, coefficient of determination. The obstacles faced at Togamas Bandung are the lack of space and making it difficult to arrange displays, product especially interior displays which are used to organize various types of products in one display with large quantities and the lack of employee attention regarding product in inputting or scanning product. While the efforts made at Togamas Supratman Bandung, namely by reducing the number of displays, returning to distributors, checking scanned of products.